2016
DOI: 10.1016/j.neuron.2016.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Context Processing and the Neurobiology of Post-Traumatic Stress Disorder

Abstract: Summary Progress in clinical and affective neuroscience is redefining psychiatric illness as symptomatic expression of cellular/molecular dysfunctions in specific brain circuits. Post-traumatic stress disorder (PTSD) has been an exemplar of this progress, with improved understanding of neurobiological systems subserving fear learning, salience detection, and emotion regulation explaining much of its phenomenology and neurobiology. However, many features remain unexplained and a parsimonious model that more ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
351
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 361 publications
(375 citation statements)
references
References 207 publications
(240 reference statements)
21
351
0
3
Order By: Relevance
“…Furthermore, the uncinate fasciculus connects the (lateral) prefrontal cortices to the hippocampus, a structure important for contextualizing, including discriminating between threatening and safe contexts. 50 Posttraumatic stress disorder has been associated with dysregulations in context processing, 51 such as enhanced fear generalization 52 and impaired contextual extinction learning 3 and safety learning. 53 Notably, these processes of contextualization depend on the hippocampus and its communication with the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the uncinate fasciculus connects the (lateral) prefrontal cortices to the hippocampus, a structure important for contextualizing, including discriminating between threatening and safe contexts. 50 Posttraumatic stress disorder has been associated with dysregulations in context processing, 51 such as enhanced fear generalization 52 and impaired contextual extinction learning 3 and safety learning. 53 Notably, these processes of contextualization depend on the hippocampus and its communication with the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly implicated neurocircuit model in PTSD involves the fear-associated learning circuitry [37]. In both humans and rodents, fear learning can be examined within the framework of classical (Pavlovian) fear conditioning, where an aversive stimulus (unconditioned stimulus; e.g., electric shock) is paired with a neutral stimulus (conditioned stimulus; e.g., a tone), resulting in the neutral stimulus eliciting a conditioned fear response (increased freezing, fear-potentiated startle, or skin conductance response).…”
Section: Fear Learning/threat Detection Circuitrymentioning
confidence: 99%
“…Symptom clusters include intrusive reexperiencing symptoms (memories of trauma, nightmares, flashbacks); avoidance of trauma-related thoughts, memories, contexts or cues; negative mood and cognition; and hyperarousal/hypervigilance [1]. In recent years, multiple studies have examined brain regions involved in PTSD symptomatology in an effort to better understand the underlying mechanisms and to develop more effective treatments [2, 3]. In this mini-review, we focus on three key neural circuits that have been implicated in the pathophysiology and symptom development in this disorder, namely, fear learning/threat detection, context processing and emotion regulation circuits.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this suggestion, prior research has demonstrated that threat increases aversive prediction error signal in the ventral striatum, indicating that anxiety may bias the predictive learning of threats to promote survival (Robinson et al 2013a). In the context of anxiety disorders, however, it may be that these responses are exaggerated and/or perpetual, thus contributing to the maintenance of an anxious state (Liberzon and Abelson 2016); this proposal is in line with the finding that visual working memory capacity increases as trait anxiety increases (Moriya and Sugiura 2012). However, future research would benefit from further elucidating the differences between adaptive and maladaptive responding, as some research suggests anxiety disorder patients exhibit impairments in visuospatial short-term memory performance (Jelinek et al 2006;O'Toole et al 2015).…”
Section: Visuospatial Working Memorymentioning
confidence: 99%